Experimental Study of an Aluminum-Polysilicon Thermopile for Implementation of Airflow Sensor on Silicon Chip - Ayub Subandi; Irman Idris; Adang Suwandi Ahmad (Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
A multi-directional airflow sensor has been realized. The essential part of the considered sensor is a thermopile configuration, which enables the measurement of flow speed and flow direction. The thermopile is a series arrangement of eight thermocouples. A thermocouple converts a difference in temperature into an electrical signal, by means of the Seebeck effect . The thermocouples are made of aluminum-N-type polysilicon junctions. The incoming flow is heated and the degree of heat transfer by convection to the flow, depends on the speed of the flow; the faster the flow the smaller the heat transfer, which leads to a smaller (Seebeck) output voltage of the thermopiles. After signal conditioning - i.e., filtering and amplification by means of an amplification system - the electrical output signals of the thermopiles are further signal-processed by applying analog-to-digital signal conversion, so that finally the flow speed and the flow direction can be properly displayed on a computer screen. The measured values of the Seebeck coefficient or thermopower (S) were in the range of: 0.43 to 0.68 mV/K which are in good agreement with the values found in the literature: 0.5 to 0.7 mV/K. Moreover, it was found that the flow speed Uï‚¥ is proportional to the reciprocal value of the square of the output voltage of the outgoing thermopile.